Factors predicting survival in ALS: a multicenter Italian study - Calvo, Andrea; Moglia, Cristina; Lunetta, Christian; Marinou, Kalliopi; Ticozzi, Nicola; Ferrante, Gianluca Drago; Scialo, Carlo; Sorarù, Gianni; Trojsi, Francesca; Conte, Amelia; Falzone, Yuri M.; Tortelli, Rosanna; et al. (Journal of neurology, 2017)
The aim of this multicenter, retrospective study is to investigate the role of clinical characteristics and therapeutic intervention on ALS prognosis. The study included patients diagnosed from January 1, 2009 to December 31, 2013 in 13 Italian referral centers for ALS located in 10 Italian regions. Caring neurologists collected a detailed phenotypic profile and follow-up data until death into an electronic database. One center collected also data from a population-based registry for ALS. 2648 incident cases were collected. The median survival time from onset to death/tracheostomy was 44 months (SE 1.18, CI 42–46). According to univariate analysis, factors related to survival from onset to death/tracheostomy were: age at onset, diagnostic delay, site of onset, phenotype, degree of certainty at diagnosis according to revised El Escorial criteria (R-EEC), presence/absence of dementia, BMI at diagnosis, patients’ provenance. In the multivariate analysis, age at onset, diagnostic delay, phenotypes but not site of onset, presence/absence of dementia, BMI, riluzole use, R-EEC criteria were independent prognostic factors of survival in ALS. We compared patients from an ALS Registry with patients from tertiary centers; the latter ones were younger, less frequently bulbar, but more frequently familial and definite at diagnosis. Our large, multicenter study demonstrated the role of some clinical and demographic factors on ALS survival, and showed some interesting differences between referral centers’ patients and the general ALS population. These results can be helpful for clinical practice, in clinical trial design and to validate new tools to predict disease progression.